Efficacy Of Multigrain Supplementation In Type 2 Diabetes Mellitus: A Randomized Human Intervention Trial - Mohd Ariffin, Nur Anis (2024)
The study is aimed to determine the effects of multigrain supplementation on (1) glycemic control; (2) cardiometabolic profile; (3) peripheral antioxidant and oxidative stress status, nutritional status and QoL; and (4) safety, compliancy and tolerability among the T2DM patients.